PENGARUH BOARD DIVERSITY, CEO CHARACTERISTICS DAN BOARD COMMITTEES TERHADAP FIRM PERFORMANCE PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rian Rizki Hidayat; Henny Setyo Lestari; Farah Margaretha (LPPM STIE Muhammadiah Bandung, 2022)
The research assesses the impact of board diversity, CEO characteristics, and board committees on the firm performance of the Indonesia stock exchange (IDX). To test the effects of this characteristic, data samples were obtained from 39 companies from 2017 to 2021, using the data panel regression model. The findings suggest that there are the effects of board diversity associated with board size and independent share against ROA then the independent share and the women share against Tobin's Q. Furthermore, the firm performance can be affected by CEO Characteristics especially by CEO age variables which affect ROA and Tobin's Q. In the case of board committees, the audit committee is found to have an effect on Tobin's Q but not on ROA. The remuneration committee has significant impact on ROA but not on Tobin's Q and nomination committee affected ROA and Tobin's Q. Based on these findings, it can be said that increasing corporate governance practices from a banking company registered in IDX will enhance its performance and value in that corporate. Keywords : Firm Performance; Board Diversity; CEO Characteristics; Board Committees; Indonesia Stock Exchange